Anatomical Cystocele Recurrence: Development and Internal Validation of a Prediction Model. Issue 5 (May 2016) - Vergeldt, Tineke F. M.; van Kuijk, Sander M. J.; Notten, Kim J. B.; Kluivers, Kirsten B.; Weemhoff, Mirjam
Abstract : Abstracted from Obstet Gynecol 2016;127:341–347 Pelvic organ prolapse (POP) surgery has high reoperation rates. Anatomic recurrence rates after surgery reported in the literature range from 31% to 59%.